The Effect of Fixed Asset Turnover and Working Capital Turnover on Profitability - Gita Puspita; Maya Arisandy; Lydia Octaviani (JFBA: Journal of Financial and Behavioural Accounting, 2021)
This study examines the effect of fixed asset turnover and working capital turnover on profitability. The object of this research is food and beverage companies on the Indonesia Stock Exchange in 2014 - 2018. 14 companies were sampled by purposive sampling techniques. The method used in this study is quantitative method with secondary data. The data analysis technique in this study uses multiple regression analysis. The results of this study show that the turnover of fixed assets and the simultaneous turnover of working capital have an effect on ROA. The turnover of fixed assets has a positive influence on the ROA, and the partial turnover of working capital has no effect on the ROA.